In-depth analysis of data from the RAS-ALS study reveals new insights in rasagiline treatment for amyotrophic lateral sclerosis - Schuster, Joachim; Dreyhaupt, Jens; Mönkemöller, Karla; Dupuis, Luc; Dieterlé, Stéphane; Weishaupt, Jochen H.; Kassubek, Jan Rainer; Petri, Susanne; Meyer, Thomas; Großkreutz, Julian; Emmer, Alexander; Herrmann, Andreas; et al. (European journal of neurology, 2024)
Background and purpose: In 2016, we concluded a randomized controlled trial testing 1 mg rasagiline per day add-on to standard therapy in 252 amyotrophic lateral sclerosis (ALS) patients. This article aims at better characterizing ALS patients who could possibly benefit from rasagiline by reporting new subgroup analysis and genetic data. Methods: We performed further exploratory in-depth analyses of the study population and investigated the relevance of single nucleotide polymorphisms (SNPs) related to the dopaminergic system. Results: Placebo-treated patients with very slow disease progression (loss of Amyotrophic Lateral Sclerosis Functional Rating Scale–Revised [ALSFRS-R] per month before randomization of ≤0.328 points) showed a per se survival probability after 24 months of 0.85 (95% confidence interval = 0.65–0.94). The large group of intermediate to fast progressing ALS patients showed a prolonged survival in the rasagiline group compared to placebo after 6 and 12 months (p = 0.02, p = 0.04), and a reduced decline of ALSFRS-R after 18 months (p = 0.049). SNP genotypes in the MAOB gene and DRD2 gene did not show clear associations with rasagiline treatment effects. Conclusions: These results underline the need to consider individual disease progression at baseline in future ALS studies. Very slow disease progressors compromise the statistical power of studies with treatment durations of 12–18 months using clinical endpoints. Analysis of MAOB and DRD2 SNPs revealed no clear relationship to any outcome parameter. More insights are expected from future studies elucidating whether patients with DRD2CC genotype (Rs2283265) show a pronounced benefit from treatment with rasagiline, pointing to the opportunities precision medicine could open up for ALS patients in the future.
Online verfügbar: 19. Januar 2024